2023
DOI: 10.1111/1365-2656.13924
|View full text |Cite
|
Sign up to set email alerts
|

Human land‐uses homogenize stream assemblages and reduce animal biomass production

Abstract: Human land‐use change is a major threat to natural ecosystems worldwide. Nonetheless, the effects of human land‐uses on the structure of plant and animal assemblages and their functional characteristics need to be better understood. Furthermore, the pathways by which human land uses affect ecosystem functions, such as biomass production, still need to be clarified. We compiled a unique dataset of fish, arthropod and macrophyte assemblages from 61 stream ecosystems in two Neotropical biomes: Amazonian rainfores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Although recent research has begun quantifying how human land-use intensi cation alters biodiversity [21][22][23] , analyses of how habitat complexity can mitigate such impacts are still lacking. Here we showed that sites with high-habitat complexity supported, on average, 10% more insect genera than sites with low-habitat complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent research has begun quantifying how human land-use intensi cation alters biodiversity [21][22][23] , analyses of how habitat complexity can mitigate such impacts are still lacking. Here we showed that sites with high-habitat complexity supported, on average, 10% more insect genera than sites with low-habitat complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, water temperature was not available in our dataset and we only have information on air temperature. We recognize that air temperature cannot fully represent the thermal regime of the stream/river, but air-and water temperature are correlated 52 and many studies reported strong impacts of air temperature on aquatic biodiversity 3,22,23,26 . We modeled log-richness and log-density using a normal distribution, and LCBD ecoregional and LCBD national using beta distribution in the R package 'glmmTMB' 53 .…”
Section: Statistical Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Pervasive land use change is among the primary causes of biodiversity loss and food web simplification, altering ecosystem functioning worldwide (Etard et al 2022;Kemp et al 2023;Moi et al 2023). The maintenance of healthy functioning ecosystems and high species diversity under increasing human pressure relies on food web rewiring and the ability of animals to shift their diet in disturbed ecosystems with scarce resources (Lu et al 2016;Kemp et al 2023).…”
mentioning
confidence: 99%